2018
DOI: 10.3390/su10041041
|View full text |Cite
|
Sign up to set email alerts
|

Doing Well or Doing Good: The Relationship between Corporate Social Responsibility and Profit in Romanian Companies

Abstract: The traditional goal of a company is to earn profit to pay its shareholders, but, nowadays, for the business to be sustainable in the long term, a strategy of Corporate Social Responsibility (CSR) activities is needed to meet stakeholder demands, respect ethical principles and give an appropriate answer to organizational stakeholders. The objective of the paper is to identify how strong the correlation between CSR and profit is, and how companies behave in the periods they have losses, whether they continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 80 publications
(79 reference statements)
6
110
1
6
Order By: Relevance
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…that analyzed whether credit ratings, such as Standard and Poor's, take sustainability performance into account;Liang, Chang, and Shao (2018) that, while not analyzing the financial performance of banks using commonly employed variables based on revenue or assets, sought to determine whether sustainable banks are more cost efficient than their counterparts; and Xiao, Wang, van der Vaart, and van Donk (2018) that determined if country-level sustainability can be a moderating variable in the CSP-CFP relationship Hategan et al, 2018;Kim & Lee, 2018;Liang et al, 2018;Shin et al, 2016;Zhao et al, 2018;Adegbite et al, 2018;Cherian et al, 2019;Xie et al, 2018)…”
mentioning
confidence: 99%
“…Thus, CSR is becoming important in both academia and practice [2][3][4][5][6]. A number of studies suggest that CSR is positively related to firm value [2,4,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Some studies even find a negative relationship between CSR and firm value [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Through CSR investment, enterprises can attract responsible consumers, obtain financial resources from investors with strong social responsibility, facilitate financing, or help struggling companies to recover from financial distress [8][9][10][11]. Scholars have found that CSR is positively related to financial performance and that CSR can improve stakeholder interests, ultimately leading to better financial performance [12][13][14]. On the contrary, failure to meet the expectations of stakeholders creates fear in the market and ultimately a loss in profitability [15].…”
Section: Literature Reviewmentioning
confidence: 99%